P5007 Systems biology approach provides novel insights into gene networks controlling tenderness and meat quality traits across French beef breeds. (1st September 2016) - Ramayo-Caldas, Y.; Renand, G.; Ballester, M.; Saintilan, R.; Rocha, D.
Abstract: Several studies focusing on Warner-Bratzler shear force (WBSF) have been performed to identify markers associated with beef meat tenderness. However, these studies have not explored the interactions among genes associated with WBSF. The main goal of our study was to identify a common set of interacting genes associated with tenderness and meat quality traits across Charolais, Limousin and Blonde d'Aquitaine beef breeds by combining genetic and transcriptomics information. First, the Association Weight Matrix (AWM) approach was used to identify genes co-associated with tenderness and meat quality traits across the previously mentioned breeds. This multi-trait approach was initially applied for each breed and 17 phenotypes. Afterward, across breeds' comparisons were performed at functional and AWM levels. Genetic heterogeneity was observed, and most of the variants segregated within rather than across breeds. A total of 206 genes (∼ 8% in each breed) were shared across the three breeds, genetic variants mapping within those common genes explained around the 28–30% of the WBSF phenotypic variance. In a second step, we integrated longissimus dorsi muscle RNASeq data considering only 121 of the 206 genes expressed in muscle. To prioritize the candidate gene selection, integrative approaches were also implemented to systematically compare the covariation of gene expression with the phenotypic variation of WBSF. Given confidence in the reliability of the results, well-known candidate genes, as well as new candidate genes, regulators and pathways affecting tenderness and meat quality traits were identified. Our results suggest that systems biology approaches increase the power to identify and prioritize candidate genes beyond the "traditional" one-dimensional approach used to identify genes affecting single traits. Further studies targeting genetic variants within the common genes, their pathways, regulators and interactions might lead to the discovery of functional mutations to guide genomic selection in a beef multi-breed context.